PITX2 gain-of-function mutation associated with atrial fibrillation alters mitochondrial activity in human iPSC atrial-like cardiomyocytes - Benzoni, Patrizia; Da Dalt, Lorenzo; Elia, Noemi; Popolizio, Vera; Cospito, Alessandro; Giannetti, Federica; Dell’Era, Patrizia; Olesen, Morten S.; Bucchi, Annalisa; Baruscotti, Mirko; Norata, Giuseppe Danilo; Barbuti, Andrea (Frontiers in Physiology, 2023)
Atrial fibrillation (AF) is the most common cardiac arrhythmia worldwide; however, the underlying causes of AF initiation are still poorly understood, particularly because currently available models do not allow in distinguishing the initial causes from maladaptive remodeling that induces and perpetuates AF. Lately, the genetic background has been proven to be important in the AF onset. iPSC-derived cardiomyocytes, being patient- and mutation-specific, may help solve this diatribe by showing the initial cell-autonomous changes underlying the development of the disease. Transcription factor paired-like homeodomain 2 (PITX2) has been identified as a key regulator of atrial development/differentiation, and the PITX2 genomic locus has the highest association with paroxysmal AF. PITX2 influences mitochondrial activity, and alterations in either its expression or function have been widely associated with AF. In this work, we investigate the activity of mitochondria in iPSC-derived atrial cardiomyocytes (aCMs) obtained from a young patient (24 years old) with paroxysmal AF, carrying a gain-of-function mutation in PITX2 (rs138163892) and from its isogenic control (CTRL) in which the heterozygous point mutation has been reverted to WT. PITX2 aCMs show a higher mitochondrial content, increased mitochondrial activity, and superoxide production under basal conditions when compared to CTRL aCMs. However, increasing mitochondrial workload by FCCP or β-adrenergic stimulation allows us to unmask mitochondrial defects in PITX2 aCMs, which are incapable of responding efficiently to the higher energy demand, determining ATP deficiency.